NEGOTIATING MULTIPLE IDENTITIES: RELIGIOUS MARRIAGE AS SOCIAL PRACTICE AMONG MUSLIMS IN THE NETHERLANDS - Saenong, Farid F. (Institut Agama Islam Negeri Bone, 2025)
Building upon extensive ethnographic fieldwork conducted across various cities and towns in the Netherlands, this study aims to examine the practices of religious marriage among Muslim communities. By religious marriage, this paper refers to any kind of Muslim marriages that are not officially registered to the local Municipal or gementee in the Netherlands. It is widely known that the institution of marriage lies at the centre of Muslim family law for the status of marriage will definitely determine all other kinds of Muslim personal law. This paper presents ethnographic data that have been collected from interviews with Muslim wedding couples, extended families, local Imams, and officials in the Netherlands. As the problem of technical terms exists in the classical discourses of religious marriage in Fiqh (Islamic law), discussions on religious marriage technical terms found from books or practices on the ground from many Muslim countries, have enriched the theoretical discourses of this unofficial marriage. The research shows that Muslim couples in the Netherlands often conclude religious marriages without civil registration due to administrative barriers, economic motives, polygyny, under-age traditions, and financial costs. These unions are viewed as valid under Islamic law, even without state recognition. Importantly, couples do not reject Dutch law but see marriage as a personal religious contract. The practice reflects continuity from countries of origin, adapted to Dutch circumstances, creating a socio-legal dynamic where Islamic and secular law coexist but not always harmoniously.